AFRICAN MUSIC ON L.P. AN ANNOTATED DISCOGRAPHY, by Alan P. Merriam, Northwestern University Press, Evanston, 1970. pp. 200. - Tracey, Hugh (International Library of African Music, 1972)
pages: 116
Keywords: African Music